Loyalty program and its influence on customer loyalty on mobile service with customer satisfaction as a mediating variable - Mulyadi Raf; Agus Syarif (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This study aims to analyze 1) the influence of loyalty program benefits on customer satisfaction, 2) the influence of loyalty program on customer loyalty, 3. the influence customer satisfaction on customer loyalty, and 4) the role of customer satisfaction in mediating the relationships of the customer loyalty program and customer loyalty to mobile service providers in Jambi City. To test the benefits of the constructs, a model was developed as a conceptual framework of the research. A total of 202 samples were collected from the mobile user population in Jambi city. Structural Equation Modeling (SEM) with Smart PLS was applied to assess the research model and to test the hypothesis. The result confirmed that the influence of loyalty program benefits directly and significantly affects customer loyalty at coefficient path 0,237 (t statistics = 2,669 < table 1, 96). Customer perceptions significantly affects customer satisfaction at coefficient path 0.625 (t statistical = 2,669 > T table 1, 96). Customer satisfaction also has a significant effect on customer loyalty at path coefficients 0.256 (t stats = 2,893 > T table = 1, 96), and it partly mediates the relationship between Loyalty Programs and customer loyalty